Development and Infrastructure in Developing Countries: A 10–Year Reflection: Proceedings of the 10th International Conference on Development and Investment in Infrastructure (DII 2024, 24-26 July 2024, Livingstone, Zambia) (Taylor & Francis, 2024)
Development and Investment in Infrastructure in Developing Countries. A 10-Year Reflection includes the contributions to the 10th International Conference on Development and Investment In infrastructure (DII-2024, Livingstone, Zambia, 24-26 July 2024). The papers discuss, evaluate and devise ways of maximising the benefits of infrastructure development and achieve outputs that will inform policy and wider development goals. This Open Access book is invaluable to leaders, researchers, practitioners, and stakeholders involved or interested in infrastructure development in developing countries.